Cardioprotective effects of metformin and vildagliptin in adult rats with insulin resistance induced by a high-fat diet - Nattayaporn Apaijai (2018)
Insulin resistance has been shown to be associated with cardiac sympathovagal imbalance, myocardial dysfunction, and cardiac mitochondrial dysfunction. Whereas metformin is a widely used antidiabetic drug to improve insulin resistance, vildagliptin is a novel oral antidiabetic drug in a group of dipeptidyl peptidase-4 inhibitors in which its cardiac effect is unclear. This study aimed to determine the cardiovascular effects of metformin and vildagliptin in rats with insulin resistance induced by high-fat diet. Male Wistar rats were fed with either a normal diet or high-fat diet (n=24 each) for 12 wk. Rats in each group were divided into three subgroups to receive the vehicle, metformin (30 mg/kg, twice daily), or vildagliptin (3 mg/kg, once daily) for another 21 d. Heart rate variability (HRV), cardiac function, and cardiac mitochondrial function were determined and compared among these treatment groups. Rats exposed to a high-fat diet developed increased body weight, visceral fat, plasma insulin, cholesterol, oxidative stress, depressed HRV, and cardiac mitochondrial dysfunction. Metformin and vildagliptin did not alter body weight and plasma glucose levels but decreased the plasma insulin, total cholesterol, and oxidative stress levels. Although both metformin and vildagliptin attenuated the depressed HRV, cardiac dysfunction, and cardiac mitochondrial dysfunction, vildagliptin was more effective in this prevention. Furthermore, only vildagliptin prevented cardiac mitochondrial membrane depolarization caused by consumption of a high-fat diet. We concluded that vildagliptin is more effective in preventing cardiac sympathovagal imbalance and cardiac dysfunction, as well as cardiac mitochondrial dysfunction, than metformin in rats with insulin resistance induced by high-fat diet. Copyright © 2012 by The Endocrine Society.